Pengelolaan Zakat di Bank Tabungan Negara Syariah Kantor Cabang Sementara Malang - muhammad rifky fath (Journal of Islamic Business Law, 2018)
This research was conducted to find out the model and management of zakat management in Bank Tabungan Negara Syariah Malang Branch Office and Zakat Management in terms of Law Number 23 Year 2011 on Zakat Management. This research is empirical research, with qualitative approach. The data used were obtained from direct interview and field observation as primary data, and some literature related to Law Number 23 Year 2011 regarding Zakat Management as secondary data. To facilitate this research, researchers used several methods of data collection, such as interviews, observation and documentation. Based on the research that has been done can be seen that the model and management of zakat management in the State Savings Bank Syariah Branch Office While Malang is appropriate because it has applied Law No. 23 of 2011 on the Management of Zakah by forming BAZIS BTN which is UPZ BAZNAS duty to manage, collect, , And utilize ZIS (Zakat, Infaq, and Shadaqah) and apply zakat management principles in Article 2 and Article 3 of Law Number 23 Year 2011 on Zakat Management.